Assessment the long-term effects of septoplasty surgery on olfactory function. (2nd October 2016) - Kilicaslan, Adem; Acar, Gul Ozbilen; Tekin, Muhammet; Ozdamar, Osman Ilkay
Abstract: Objectives: This research aimed to evaluate pre-operatively and post-operatively the olfactory function of patients who had undergone surgery in our clinic for chronic nasal blockage via the Connecticut Chemosensory Clinical Research Center (CCCRC) smell test. Method: Thirty-seven patients (24 females, 13 males) were enrolled in this study. All had undergone surgery in our clinic due to chronic nasal blockage (not for smell dysfunction), having been diagnosed with septal deviation in conjunction with concha bullosa and/or inferior turbinate hypertrophy. This is a prospective study without a control group. The mean age was 33.74 ± 8.98 (range =19–54). All of the operations were performed under general anesthesia. CCCRC smell tests were performed on every patient before the operation and at post-operative 1st week, 6th week, 6th month, and 1st year. Results: In this study, we found that septoplasty, in conjunction with middle concha surgery and/or inferior concha radiofrequency, did not affect the olfactory function negatively. Conclusion: Although nasal surgery has the potential to affect the smell function negatively, it was found that olfactory function was not affected after the surgery during a considerably long follow-up period. Moreover, an improvement in smell function was detected at post-operative 6th month and 1st year.